The home blacksmith - Ridgway, Ryan (Fox Chapel Publishing Company, Inc., 2020)
"The author gives detailed information on the science behind metalworking, how metal moves, and how to work with heated metal. He explains the origins of blacksmithing, the required equipment, and safety precautions before presenting step-by-step illustrated instructions for making useful and decorative items for indoor and outdoor use in the home, in the yard, and on the farm"--